Website quality evaluation: review of models - Morais, Elisabete Paulo (2015)
Websites quality is strategically important for organizations and for their clients’ satisfaction. The rapid growth of web applications increases the need to evaluate web applications quantitatively and qualitatively. When you attempt to evaluate websites, many different evaluation methods can be used. This paper analyzes and presents different quality models in order to perceive which is the most appropriate, depending on the situation.